Molecular regulation and therapeutic targeting of MYCN in neuroblastoma: a comprehensive review - Chen, Yi; Yang, Huixian; Xiao, Lirong; Yan, Naihong; Zhang, Ming (Frontiers in Cell and Developmental Biology, 2025)
MYCN amplification defines a highly aggressive subtype of neuroblastoma and is strongly associated with poor clinical outcomes. Due to the intrinsically disordered structure of the N-Myc protein, it remains largely undruggable. This review provides a comprehensive summary of the molecular regulatory network surrounding MYCN, including upstream pathways, key cofactors, and downstream effectors involved in cell cycle control, metabolic reprogramming, and ferroptosis. We further discuss the roles of epigenetic modulators, noncoding RNAs, and positive feedback loops in sustaining MYCN-driven oncogenic programs. Emerging therapeutic strategies such as PROTACs, metabolic inhibitors, immune-based approaches, and RNA-targeting technologies offer promising alternatives to direct MYCN inhibition. This review aims to provide a theoretical foundation for future development of precise and effective therapies targeting MYCN-amplified neuroblastoma.